Superposed Deformations of the Ketilidian Gneisses in the Sárdloq Area, South Greenland. - Windley, B. F. (Meddelelser om Grønland, 1966)
A large part of the Sardloq area comprises intercalated horizons of homogeneous gneiss, veined gneiss and banded gneiss of Precambrian age. The gneisses were deformed during the Ketilidian orogeny by three phases of folding, F1-F3 . F1 are in the form of mesoscopic intrafolial folds in varying states of preservation within the regional foliation, S1. F2 are mesoscopic and macroscopic folds that have a shallow plunge to the NE and SW, where unaffected by the third folding. Asymmetrical, similar, disharmonic folds with curviplanar axial planes but constantly oriented axes are the characteristic F2 structures formed under strong lithological control mostly in the veined gneiss horizons under syn-migmatisation and amphibolite facies conditions. The crystallisation of constituent minerals taking place under syn- to post-kinematic conditions outlasted the deformation. S2 axial plane structures are rarely developed. F3 folds have a constant orientation with vertical axial planes and plunge variably to the NW or SE. The F3 folds are in the form of a macroscopic buckling of the S1 foliation formed under post-migmatisation and epidote-amphibolite facies conditions. A tectonic melange was locally formed in response to the third phase movements. A structural correlation is made with neighbouring areas. It is suggested that the metamorphism and migmatisation are diachronous with respect to the fold phases, arriving during the third folding at a higher level in the Nanortalik area to the SE.